Implicações do fenômeno Big Data na tomada de decisão baseada em dados em uma cooperativa de crédito - Baú, Jean Michel (My University, 2019)
With the exponential growth in the volume of data to be managed and analyzed by companies in the last decades, more complexity is added to the decision making. In addition to volume, they also multiply as data sources and formats. This context acquires the contours of what is called a Big Data phenomenon. In turn, Data-Driven Decision Making has the potential to change as a business strategy; at the same time that it requires greater preparation of the professionals responsible for decision making in organizations. In this context, the objective of this research was to analyze decisionmaking practices based on data associated with the analysis of data characterized as Big Data. The method adopted was a unique, exploratory and qualitative case study, developed with a cooperative credit institution. This research revealed that the dimensions of the Big Data (Volume, Variety, Velocity, Veracity and Value) are synergistically associated with the steps of the process of extracting insights from the data for decision making (Acquisition and Registration, Extraction, Cleaning and Comments; Aggregation and Representation, Modeling and Analysis and Interpretation) in the case studied. It was also revealed that the decision-making in the data-driven context occurs considering subjective elements, such as intuition. It was also identified the presence of four filters or stages present in the process of datadriven decision making: accountability, situational factors, organizational culture and political relationship. From the results, a Data-Driven Decision-Making framework was designed for organizations that deal with data that has the dimensions of Big Data.
Com o crescimento exponencial do volume de dados digitais à disposição das empresas nas últimas décadas, emergem novos desafios à tomada de decisão. Além do volume, também se multiplicam as fontes e formatos dos dados. Este contexto adquire assim contornos do que é chamado de fenômeno Big Data. Por sua vez, a tomada de decisão baseada em dados tem potencial para mudar as estratégias empresariais; ao mesmo tempo em que exige maior preparo dos profissionais responsáveis pela tomada de decisão nas organizações. Neste contexto, o objetivo deste trabalho foi analisar as práticas decisórias baseadas em dados associadas à análise de dados caracterizados como Big Data. O método adotado foi um estudo de caso único, exploratório e qualitativo, desenvolvido junto a uma instituição cooperativa de crédito. Esta pesquisa revelou que as dimensões do Big Data (Volume, Variedade, Velocidade, Veracidade e Valor) são sinergicamente associadas as etapas do processo de extração de insights dos dados para tomada de decisão (Aquisição e Registro; Extração, Limpeza e Comentários; Integração; Agregação e Representação; Modelagem e Análise e Interpretação) no caso estudado. Revelou-se ainda que a tomada de decisão no contexto data-driven ocorre considerando elementos subjetivos, como a intuição. Identificou-se ainda a presença de quatro filtros ou etapas presentes no processo de tomada de decisão data-driven: alçadas de responsabilidade, fatores situacionais, cultura organizacional e relacionamento político. Dos resultados desenhou-se um framework orientativo a prática de tomada de decisão Data-Driven, em organizações que lidam com dados que possuam as dimensões do Big Data.
Keywords: Big data; Framework (Arquivo de computador); Processo decisório; Big data; Framework (Computer program); Decision making